2002
DOI: 10.1103/physreve.66.057101
|View full text |Cite
|
Sign up to set email alerts
|

Sweeny and Gliozzi dynamics for simulations of Potts models in the Fortuin-Kasteleyn representation

Abstract: We compare the correlation times of the Sweeny and Gliozzi dynamics for two-dimensional Ising and three-state Potts models, and the three-dimensional Ising model for the simulations in the percolation representation. The results are also compared with Swendsen-Wang and Wolff cluster dynamics. It is found that Sweeny and Gliozzi dynamics have essentially the same dynamical critical behavior. Contrary to Gliozzi's claim [Phys. Rev. E 66, 016115 (2002)], the Gliozzi dynamics has critical slowing down comparable t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 14 publications
3
16
1
Order By: Relevance
“…Our data resolve the discrepancies between previous works [9,[14][15][16][17][18][19][20], which can now be understood as arising from corrections to scaling.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Our data resolve the discrepancies between previous works [9,[14][15][16][17][18][19][20], which can now be understood as arising from corrections to scaling.…”
Section: Discussioncontrasting
confidence: 54%
“…And since there is good reason to believe (see Section 5.2 below) that C 1 does indeed have a significant overlap with the slowest mode in the Swendsen-Wang algorithm, this suggests that Wang's observable is not interpretable within the standard Swendsen-Wang algorithm, but rather represents a new slow mode in the variant algorithm. 7 A pure power-law fit to the raw data of Wang, Kozan and Swendsen [20] yields a decent χ 2 if (and only if) L min ≥ 32. Our preferred fit is L min = 32, and yields z int,E = 0.502 ± 0.012 (χ 2 = 0.440, 1 DF, level = 50.7%).…”
mentioning
confidence: 99%
“…Typically, trial configurations are randomly chosen, as in the standard Metropolis algorithm, so that the trial configuration selection matrix T ij is symmetric. The acceptance probability for a move from state i to state j is then , (18) which implies that the probability of configuration i is given by 1/g(E i ). Because the density of states is g(E i ), this eventually leads to a flat histogram in energy space-that is, a "random walk" in energy space.…”
Section: Multicanonical Methodsmentioning
confidence: 99%
“…Because the clusters can be arbitrarily large at the critical temperature in this algorithm, the new configuration can differ substantially from the original one. In Monte Carlo simulations of the 2D Ising model performed with this algorithm, 17,18 researchers found that critical slowing down was significantly reduced.…”
Section: Cluster Accelerationmentioning
confidence: 99%
See 1 more Smart Citation